A vertebrate cytokine primer for eco‐immunologists. (26th March 2014) - Zimmerman, Laura M.; Bowden, Rachel M.; Vogel, Laura A.; Tschirren, Barbara
Summary The field of eco‐immunology seeks to address the causes and consequences of natural variation in immune responses. Recently, the development of more immunological resources for nonmodel systems along with the growing availability of genomic data has made it feasible to explore more complex immunological differences in nonmodel systems. Cytokines are small molecular weight proteins that are the major signalling molecules of the immune system. Studies in mice and humans have demonstrated the importance of tightly regulated cytokine signalling, and thus, cytokines may play a major, unexplored role in explaining natural variation in immune responses. In this review, we highlight cytokines that are likely to be important for eco‐immunology studies and what is currently known about their presence or absence in the major vertebrate groups. We also explore what types of questions an eco‐immunologist might ask involving cytokines and discuss potential ways to measure cytokines in nonmodel systems. Inclusion of cytokines in eco‐immunology will advance the field as it will help us to better understand mechanisms behind both natural variation in immune responses and how different taxa respond to immune challenges.